EFEKTIFITAS BLENDED LEARNING DALAM PROSES PEMBELAJARAN - Nurul Hidayah (Majelis Pendidikan Aceh, 2020)
As the rapid development of Science and Technology, especially in the Millennial Era, this certainly has influenced the learning methods used in education. E-learning programs are increasingly encouraged to answer the challenges of accelerating the global era through programs that are perceived as fast, efficient with targets that seem to want to penetrate space and time so that slowly shifting face-to-face methods are considered by some as an effective learning process. This paper wants to examine how the e-learning method approach is compared to the face-to-face method in the learning process. Which is more efficient and effective in increasing competency for students without being limited to the level of participants in the learning process through the pedagogical approach, andragogy and the role of the facilitator, but in general we will see how organizing the education process through the two systems in question. From the author's observations supported by related literacy, these two approaches in principle have their advantages and disadvantages, so that to produce an effective approach both can be combined in the form of a blended learning system.